Delivery of Splice Switching Oligonucleotides by Amphiphilic Chitosan-Based Nanoparticles - Moreno, PM (2016)
Splice switching oligonucleotides (SSOs) are a class of single-stranded antisense oligonucleotides (ssONs) being used as gene therapeutics and demonstrating great therapeutic potential. The availability of biodegradable and biocompatible delivery vectors that could improve delivery efficiencies, reduce dosage, and, in parallel, reduce toxicity concerns could be advantageous for clinical translation. In this work we explored the use of quaternized amphiphilic chitosan-based vectors in nanocomplex formation and delivery of splice switching oligonucleotides (SSO) into cells, while providing insights regarding cellular uptake of such complexes. Results show that the chitosan amphiphilic character is important when dealing with SSOs, greatly improving colloidal stability under serum conditions, as analyzed by dynamic light scattering, and enhancing cellular association. Nanocomplexes were found to follow an endolysosomal route with a long lysosome residence time. Conjugation of a hydrophobic moiety, stearic acid, to quaternized chitosan was a necessary condition to achieve transfection, as an unmodified quaternary chitosan was completely ineffective. We thus demonstrate that amphiphilic quaternized chitosan is a biomaterial that holds promise and warrants further development as a platform for SSO delivery strategies.